1984
DOI: 10.1079/bjn19840103
|View full text |Cite
|
Sign up to set email alerts
|

Hexose transport and mucosal morphology in the small intestine of the zinc-deficient rat

Abstract: 1. Immature male Wistar rats were given a zinc-depleted semi-synthetic diet (2 mg Zn/kg diet) for 4 weeks.Control groups received a similar diet containing 60 mg Zn/kg diet, either ad lib. or in amounts matched to the consumption of the Zn-deficient group. Rates of growth and food conversion efficiency were markedly lower in the Zn-deficient group compared to controls.2. The phloridzin-sensitive uptake of galactose and 3-0-methyl glucose by everted jejunal rings from each group was measured over a range of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 18 publications
4
22
1
Order By: Relevance
“…Such absorption studies performed at a single substrate concentration, and without reference to intestinal structural changes, do not lend themselves to investigations of absorption mechanisms at the cellular level. Our investigations, which include both kinetic and morphological studies, suggest that these mechanisms are altered in response to dietary Zn-depletion (Southon et al 1984). There also appeared to be some response to prolonged feed restriction in the control animals, in that rates of galactose transport per unit dry weight and per unit length of jejunum tended to be higher in this group of rats compared with ad lib.-fed controls.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Such absorption studies performed at a single substrate concentration, and without reference to intestinal structural changes, do not lend themselves to investigations of absorption mechanisms at the cellular level. Our investigations, which include both kinetic and morphological studies, suggest that these mechanisms are altered in response to dietary Zn-depletion (Southon et al 1984). There also appeared to be some response to prolonged feed restriction in the control animals, in that rates of galactose transport per unit dry weight and per unit length of jejunum tended to be higher in this group of rats compared with ad lib.-fed controls.…”
Section: Discussionmentioning
confidence: 58%
“…In a previous study we investigated the phloridzin-sensitive uptake of galactose and 3-0-methyl glucose in vitro by everted jejunal rings from Zn-deficient and Zn-supplemented rats. The study demonstrated that Zn-deficiency was accompanied by a marked enhancement of carrier-mediated hexose uptake in the jejunal mucosa, which appeared to result from the presence of larger numbers of carrier sites per unit dry weight of intestine (Southon et al 1984). This increased capacity to transport substrate across the brush-border membrane however does not necessarily imply an increased rate of net trans-epithelial transport.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Humidity was around 40%. Standard rat diet [20] and water were available ad libitum for the duration of the experiments. The diet consisted (in grams per kg of diet) of cornstarch 326, sucrose 326, proteins 168 (egg-white solids), lipids 80 (corn oil), fibre 40 (cellulose), vitamin mix (sigma) and mineral mix 40.…”
Section: Animalsmentioning
confidence: 99%